In-tube micro-pyramidal silicon nanopore for inertial-kinetic sensing of single molecules - Yang, Jianxin; Pan, Tianle; Xie, Zhenming; Yuan, Wu; Ho, Ho-Pui (Nature communications, 2024)
Electrokinetic force has been the major choice for driving the translocation of molecules through a nanopore. However, the use of this approach is limited by an uncontrollable translocation speed, resulting in non-uniform conductance signals with low conformational sensitivity, which hinders the accurate discrimination of the molecules. Here, we show the use of inertial-kinetic translocation induced by spinning an in-tube micro-pyramidal silicon nanopore fabricated using photovoltaic electrochemical etch-stop technique for biomolecular sensing. By adjusting the kinetic properties of a funnel-shaped centrifugal force field while maintaining a counter-balanced state of electrophoretic and electroosmotic effect in the nanopore, we achieved regulated translocation of proteins and obtained stable signals of long and adjustable dwell times and high conformational sensitivity. Moreover, we demonstrated instantaneous sensing and discrimination of molecular conformations and longitudinal monitoring of molecular reactions and conformation changes by wirelessly measuring characteristic features in current blockade readouts using the in-tube nanopore device. The authors report a strategy to achieve high S/N ratio signal readout in single molecule sensing by incorporating the inertial forces as a new channel for independently controlling the translocation parameters with high precision.